Efektivitas Pelayanan Kartu Tanda Pencari Kerja (AK.1) di Dinas Tenaga Kerja Kota Bengkulu - Rahmadhani, Fanni; Anwar, Faizal; Rosidin, Rosidin (JOPPAS: Journal of Public Policy and Administration Silampari, 2023)
The purpose of this study was "to find out the effectiveness of the job seeker's card service (AK.1) at the Bengkulu City Employment Service. The research was conducted at the Bengkulu City Employment Service Located at Jalan Basuki Rahmat No.05 kec. Queen of Samban Bengkulu. This research is a qualitative research with a descriptive approach. This research is focused on seeing whether the implementation of the Job Seeker's Card Service (AK.1) carried out by the Bengkulu City Manpower Office has been going well or not. Data collection uses Observation Techniques, Interview Techniques, Documentation Techniques with Data Analysis (Data Collection, Data Reduction, Data Presentation, Drawing Conclusions) and the results show that service procedures at the Bengkulu City Employment Service are very good. The Job Seeker's Identity Card (AK.1) is very fast and the processing fee is free or free of charge, the infrastructure needs additional facilities. Overall, the employees of the Bengkulu City Employment Service have very good competence in service and the products produced are clear. in the form of a Job Seeker's Identity Card (AK.1) and legalized. Keywords: Service Effectiveness